Heterogeneous Bimetallic Phosphide Ni2P‐Fe2P as an Efficient Bifunctional Catalyst for Water/Seawater Splitting. (28th September 2020) - Wu, Libo; Yu, Luo; Zhang, Fanghao; McElhenny, Brian; Luo, Dan; Karim, Alamgir; Chen, Shuo; Ren, Zhifeng
Abstract: Developing high‐performance and cost‐effective bifunctional electrocatalysts for large‐scale water electrolysis is desirable but remains a significant challenge. Most existing nano‐ and micro‐structured electrocatalysts require complex synthetic procedures, making scale‐up highly challenging. Here, a heterogeneous Ni2 P‐Fe2 P microsheet is synthesized by directly soaking Ni foam in hydrochloric acid and an iron nitrate solution, followed by phosphidation. Benefiting from high intrinsic activity, abundant active sites, and a superior transfer coefficient, this self‐supported Ni2 P‐Fe2 P electrocatalyst shows superb catalytic activity toward overall water splitting, requiring low voltages of 1.682 and 1.865 V to attain current densities of 100 and 500 mA cm −2 in 1 m KOH, respectively. Such catalytic performance is superior to the benchmark IrO2 || Pt/C pair and also places this electrocatalyst among the best bifunctional catalysts reported thus far. Furthermore, its enhanced corrosion resistance and hydrophilic surface make it suitable for seawater splitting. It is able to achieve current densities of 100 and 500 mA cm −2 in 1 m KOH seawater at voltages of 1.811 and 2.004 V, respectively, which, together with its robust durability, demonstrates its great potential for realistic seawater electrolysis. This work presents a general and economic approach toward the fabrication of heterogeneous metallic phosphide catalysts for water/seawater electrocatalysis. Abstract : A novel and economic strategy is developed to synthesize heterogeneous bimetallic phosphide Ni2 P‐Fe2 P as an efficient bifunctional catalyst for water/seawater splitting. Benefiting from high intrinsic activity, abundant active sites, and a superior transfer coefficient, this self‐supported Ni2 P‐Fe2 P electrocatalyst shows superb catalytic activity toward overall water splitting, together with its robust durability.